Highly Sensitive Detection of Ciprofloxacin by Photoelectrochemical Sensor Under Visible Light Based on BiPO4/BiOI Heterojunction. Issue 16 (1st January 2019) - Zhao, Mingxia; Yang, Liqin; Jiang, Junbing; Shi, Nan; Huo, Weitao; Zhao, Ziwei; Yang, Rongbao; Wang, Jingjing; Zhao, Zhiju; Li, Guanghua; Cai, Zhenyu
Abstract : Through the fast reconstruction of photogenerated carriers with low visible light absorption, the photocatalytic performance of BiOI is limited. The fabrication of BiPO4 /BiOI-X (X represented the mass percentage of BiPO4 related to the BiPO4 /BiOI heterojunction, X = 2%, 5% and 7%) heterojunction by in suit growing of BiPO4  staying at the surface of BiOI will improve the scale of absorption on visible light and divide photogenerated carriers. The structure and morphology have been detailed measured by a series of physical characterizations. The photoelectrochemical (PEC) activity of BiPO4 /BiOI composites for ciprofloxacin (CIP) detection was checked with the by means of visible light irradiation. The BiPO4 /BiOI-5% have excellent photocurrent pristine BiPO4 and BiOI. Since the PEC efficiency is greatly enhanced, which are contributed to the efficient separation of photogenerated carriers by successfully forming p-n heterojunctions. The UV-vis DRS (Diffuse reflection spectra) together with photoluminescence (PL) further proved that the BiPO4 /BiOI-5% have excellent PEC properties than other materials. The as-prepared BiPO4 /BiOI-5% exhibited wide linear range (80–7440 ng.mL −1 ) and high stability for sensing CIP, moreover, it also embraces huge application potential in the aspect of actual samples.